Resiko Remaja Thalasemia terhadap Perubahan Perilaku : Thalassemia Adolescents' Risk of Behavior Change - Halimah; Allenidekania; Fajar Tri Waluyanti (Fakultas Keperawatan Universitas Andalas, 2016)
Adolescent with chronic illness such as thalassemia can increase the risk of behavioral changes. The purpose of this study is to identify the risk of behavioral changes in adolescents with thalassemia such as anxiety, social problem and attention deficits. This study used cross sectional. Respondent consist of 43 adolescent (12-18 years old) and their parents to filled questionnaire about the related factors, anxiety, social problem, and attention deficits in thalassemia. The results shown that male adolescent have a risk to experience anxiety problem (OR 2,5), social problem (OR 1,264), and attention deficits (OR 1,185). Adolescents with Jawa and the other ethnic have a risk to experience anxiety problem (OR 0,001), social problem (0,001 and 0,365), and attention deficits (1,338 and 0,501). Another factor such as multitranfusion more than 5 years have a risk to experience anxiety problem (OR 0,001), low parent’s support with social problem (0,042), and low or middle of mother education increase attention deficits risk until 3,763 and 1,338. Nurses responsible to solve behavioral problem with current nursing intervention to prevent low quality of live in adult with thalassemia